New directions in centre‐based aged care in Australia: Responding to changing funding models and the COVID‐19 pandemic. (24th May 2022) - Hamilton, Myra; Crawford, Tonia; Thomson, Cathy; Jeon, Yun‐Hee; Bassett, Kimberley
Abstract: Objectives: Centre‐based aged care services are a key site of early intervention and support for people with dementia and their carers. This paper examines the impact of new aged care funding structures on centre‐based aged care service accessibility and delivery. It also examines the challenges and opportunities for change facing the sector in the light of the COVID‐19 pandemic. Methods: Semi‐structured interviews were conducted online with 29 managers or supervisors of centre‐based aged care services in Greater Sydney. Results: The analysis reinforced the essential role of centre‐based aged care services in improving the cognitive, physical and psychological health of older people with dementia and their carers. However, the changing funding context and the COVID‐19 pandemic have created challenges in access to centre‐based services, particularly for the most vulnerable. The challenges created by the COVID‐19 pandemic also opened opportunities for the introduction of new models of service practice to meet the individual needs of older people and their carers. Conclusions: Greater investment in, and flexibility in the funding for, centre‐based aged care services is needed to facilitate access for people with dementia and their carers and improve their health and well‐being.